MIS Essentials - Kroenke, David M. 1948- (Always learning., 2015)
Exploring how people use IS to solve business problems, this engaging introduction explains why MIS is the most important course in the business school-showing students how businesses use information systems and technology to accomplish their goals, objectives, and competitive strategy. Three unique Guides per chapter focus on the themes of ethics, security, and other timely topics; a number of illustrative cases, exercises, projects, and other aids ensure that students connect the knowledge in the text to everyday life. With a new edition now publishing each year, MIS Essentials, Fourth Edition contains fresh, new, and current material to help keep your students up to date.